'Beneficial impurities' in colloidal synthesis of surfactant coated inorganic nanoparticles. (10th December 2020) - Abutbul, Ran Eitan; Golan, Yuval
Abstract: Colloidal synthesis of nanoparticles (NP) has advanced tremendously over the past 25 years, with an increasing number of research papers introducing nanomaterials with a variety of compositions, shapes, sizes, and phases. Although much progress has been achieved, commonly used synthetic procedures often fail to reproduce results, and the fine details of the syntheses are often disregarded. Reproducibility issues in synthesis can be ascribed to the effects of impurities, trace amounts of chemical moieties which significantly affect the reaction products. Impurities in NP synthesis are rarely reported or regularly studied, despite their impact, deleterious, or beneficial. This topical review discusses several case studies of colloidal NP synthesis where the sources and the chemistry of impurities are highlighted, and their role is examined.